Role of Inflow of Resources on Economic Growth of Nepal (Economic Journal of Nepal, 2019)
This study attempts to examine the role of the inflow of resources on the economic growth of Nepal incorporating annual time-series data sets of 45 years from 1975 to 2019. The autoregressive distributed lag approach to cointegration is used to identify the long-run as well as the short-run relationship between the variables. The empirical finding indicates that there is a positive relationship between the inflow of resources and economic growth. Quantitatively, gross national saving, domestic loans, foreign loans, and export earnings have a positive impact on the economic growth in both the long-run as well as short-run for the Nepalese economy. Policies encouraging private sector participation, enlarging efficiency, and effectiveness of public sector projects, and expanding export base must be implemented.